Examining the Effect of Tax Reforms on Revenue Collection Performance in Uganda: - Turyaheebwa, Paul; Kaaya, Siraje; Turyahebwa, Abanis; Sunday, Arthur (International Journal of Research in Sociology and Anthropology (IJRSA), 2025)
This study examines the effect of tax reforms on revenue collection performance in Uganda, with a focus on the mediating role of e-tax innovation in tax administration. The research employs a quantitative approach, utilizing a cross-sectional survey design to collect data from 350 active taxpayers across various industries in the Greater Mbarara region. The study investigates the impact of tax reforms, including VAT reforms, presumptive tax regimes, and technological innovations in tax administration, on revenue collection performance. Structural Equation Modeling (SEM) was used to analyze the relationships between tax reforms and revenue collection performance. The findings reveal a positive and statistically significant relationship between tax reforms and revenue collection performance (β = 0.303, Z-value = 4.801, p < 0.001). The study also highlights the importance of e-tax innovation as a mediating factor in this relationship. The research contributes to the understanding of tax reform effectiveness in developing countries, emphasizing the role of fairness perceptions, tax education, and technological advancements in improving tax compliance and revenue collection. The findings suggest that a comprehensive approach integrating these factors is crucial for enhancing Uganda's tax system efficiency and effectiveness. This study provides valuable insights for policymakers and tax administrators in Uganda and similar developing countries, offering recommendations for improving tax reform strategies and implementation to boost revenue collection performance.